Factors Affecting the Exercise Capacity in Pediatric Primary Hypertension - Zhang, Hui; Chen, Yeshi; Zheng, Tong; Zhang, Mingming; Li, Xiaohui; Shi, Lin (Frontiers in Pediatrics, 2022)
Purpose Exercise training is crucial to the early intervention of pediatric primary hypertension (PHT). However, much less is known about exercise capacity in this disease. This work investigated the exercise capacity in pediatric PHT and analyzed the factors affecting exercise capacity. Methods The study enrolled children with PHT at the Children's Hospital Capital Institute of Pediatrics between July 2017 and July 2020. The Bruce protocol of the treadmill exercise test (TET) was used to assess exercise capacity. Multivariate ordinal logistic regression and generalized linear models were used to analyze factors affecting exercise capacity. Results Of 190 patients, 146 (76.8%) were male, and the median age was 13 (11, 14). Most children accomplished TET and achieved the submaximal heart rates (189 [99.5%]). Children with lower resting diastolic blood pressure (DBP) and 24 h average diastolic blood pressure (ADBP) could achieve a TET stage of 6 or more, whereas children with higher DBP and ADBP could only achieve a TET stage of 3 (P all < 0.05). Children with lower DBP and 24 h ADBP were also associated with greater metabolic equivalents (METs; r = −0.237, r = −0.179, P all < 0.05). The completion of TET stages was negatively associated with female (OR = 0.163), younger age (OR = 1.198), greater body mass index (BMI, OR = 0.921), and higher 24 h ADBP (OR = 0.952, P all < 0.05). In addition, METs were negatively associated with female (β = −1.909), younger age (β = 0.282), greater BMI (β = −0.134), and higher 24 h ADBP (β = −0.063, P all < 0.05). Conclusions Exercise capacity was impaired among pediatric PHT patients. Female gender, younger age, greater BMI, and higher 24 h ADBP are independently associated with the exercise capacity in pediatric PHT. These findings may help developing scientific exercise prescriptions for pediatric PHT.